2013
DOI: 10.1097/cji.0b013e3182780abc
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunotherapy Study of Prostate Cancer Patients and Resulting IgG Responses to Peptide Epitopes Predicted From Prostate Tumor-associated Autoantigens

Abstract: The immunogenicity of a cellular immunotherapy using genetically modified vaccines to express α(1,3)galactosyl epitopes (αGal) was evaluated in advanced prostate cancer (PC) patients. In this dose escalation phase I study, we report safety, feasibility, and immunologic data of an immunotherapy composed of 2 human PC cell lines engineered to express αGal epitopes (HyperAcute-Prostate, HAP, NewLink Genetics). Eight patients received up to 12 biweekly vaccinations with HAP. Enrolled patients (aged range, 53-85 y)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Characteristics of the six nonrandomized prospective cohort trials included for the review are summarized in the Table 1 . 25 , 27 , 28 , 29 , 30 , 31 Of these six studies, except for two studies having five and two groups of intervention, all other studies were single armed. Because of the aggregate nature of data, we could not identify patients positive for HLA-A0201 although the inclusion criteria among studies were similar enough to avoid significant bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the six nonrandomized prospective cohort trials included for the review are summarized in the Table 1 . 25 , 27 , 28 , 29 , 30 , 31 Of these six studies, except for two studies having five and two groups of intervention, all other studies were single armed. Because of the aggregate nature of data, we could not identify patients positive for HLA-A0201 although the inclusion criteria among studies were similar enough to avoid significant bias.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported the OS of the sample population; Hemstreet et al reported OS of 25.1 months, and Tjoa et al (1999) reported OS of 4.8 months (which are not presented here). 25 , 31 However, these reports are significantly heterogenous in nature and most probably not reliable. The study by Tjoa et al (1999) had used GM-CSF in combination with DCs and was not included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HyperAcute vaccines are made of tumour cell lines that have been genetically engineered to express the α(1,3)-galactosyltransferase enzyme in order to induce an hyperacute reaction with complement-and antibody-dependant cytotoxicity [135]. They have been tested in several malignancies including melanoma, pancreatic and prostate cancer [136][137][138] and showed encouraging results improving OS. This vaccine was further evaluated in two phase 3 clinical trials.…”
Section: Tumour Cell Vaccinesmentioning
confidence: 99%
“…Mounting evidence from both in-vitro and in-vivo studies at Precision Biologics and other research groups suggest that this process is represented mainly through a B cell response, producing the needed levels of the specific IgG1 that can bring tumor growth under control 2-5. Under normal circumstances however, the needed level of tumor antigen expression to induce the proper host response is low.…”
Section: The Host Immune Responsementioning
confidence: 99%